Brain Drain Or Brain Gain? The Impact Of Youth Migration On Nepal’s Development - Tara Prasad Bhusal (Journal of Contemporary Review, 2025)
Nepal has been experiencing an unprecedented scale of youth migration over the last decade. For many households, sending a young family member abroad for work or study has become a normal survival strategy rather than an exception. This situation has created a serious national debate: is Nepal losing its most productive human resources in the form of brain drain, or can migration still contribute positively to development as brain gain? Using secondary data from government reports, Nepal Rastra Bank publications, census data, international organizations, and existing academic studies, this paper examines the economic, social, and institutional impacts of youth migration on Nepal’s development process. Recent data indicate that more than 2.5 million Nepalis have migrated abroad during the last three years alone, while remittance inflows reached approximately NPR 1.723 trillion in fiscal year 2024/25, accounting for nearly 28.6 percent of GDP (Nepal Rastra Bank [NRB], 2025). Although remittances have played a critical role in reducing poverty, stabilizing foreign exchange reserves, and supporting household consumption, Nepal is increasingly facing labor shortages in agriculture, health, education, and technical fields. Demographic imbalance, declining productivity, weak innovation capacity, and low productive use of remittance raise serious concerns about the sustainability of remittance-led growth.This paper argues that, in the absence of strategic policies focused on domestic employment generation, quality education, skill retention, and structured diaspora engagement, youth migration in Nepal is more likely to remain a net brain drain. However, with appropriate institutional reforms and long-term planning, migration can still be transformed into brain gain. The paper concludes with policy-oriented recommendations aimed at aligning migration with Nepal’s broader development goals.